Dynamic Simulation Analysis of a Motorcycle Suspension System - Assessment of Comfort - Segla, Stefan; Roy, Sayantan (Manufacturing Technology Journal, 2020)
The paper deals with dynamic in-plane simulation analysis of a motorcycle suspension. The motorcy-cle᾿s mechanical model is considered as a visco-elastically suspended rigid body. Two types of the kinematic excitation are considered ‒ a deterministic "hat" shaped bump and stochastically uneven road characterized by its power spectral density. The simulation results for both the deterministic bump and stochastically uneven road show that significant reduction of the root mean square value of the motorcycle body centroid acceleration (comfort criterion) can be achieved by placing the lower end point of the rare spring-damper module closer to the beginning of the swinging arm and also by increasing deviation (tilt) of the spring-damper module from the vertical. The maximum improvement in the root mean square value of the motorcycle body centroid acceleration is 51.7 % for the deterministic "hat" shaped bump and 37.4 % for the stochastically uneven road. The method presented in the paper can be employed in design of both touring motorcycles, which are characterized by higher requirements of comfort, and off-road motorcycles where protection from impacts generated by bumps is important.
Keywords: Motorcycle; Suspension System; Simulation; Road Profile; Comfort